Aluminium stress in crop plants - García Oliveira, A.L.; Chander, S.; Barcelo, J.; Poschenrieder, Charlotte (Astral International Pvt. Ltd., 2016)
Aluminium (Al) toxicity has a strong negative impact on crop productivity on acid mineral soils. Liming and fertilisation frequently are insufficient to overcome the problem, especially in tropical areas with subsoil acidity. The focus on breeding for acid soil tolerance as a more sustainable tool to achieve better crop performance has strongly stimulated research into the mechanisms of Al toxicity and tolerance. Root tips have been identified as the primary target of Al toxicity in most crops, wherefore primary Al tolerance mechanisms based on exudation of strong Al-ligands also are operating there. Recent studies have already identified several genes responsible for the Al tolerance based on Al-induced root tip exudation of organic acids. In the post genomic era, genomic technologies tied together with physiology and biochemistry have made considerable further advances in our understanding of Altoxicity and tolerance mechanisms in an integrated way. However, in order to fill the still existing gap between geneticists and breeders a deeper knowledge on the Al-toxicity and tolerance mechanisms at the genetic, molecular and physiological levels is required, not only in crop plants, but also considering the large ecological diversity of naturally adapted species. This will provide a closer relation between genotyping and phenotyping tools allowing faster breeding progress. In addition to these aspects, this chapter will also provide a glance into the potential of mutagenesis and transgenic approach for Al-toxicity improvement in different plants.